Windows/Android synchronization Part 1 - Ng, Zhi Ming (2015)
Technology has been advancing rapidly over the years. Many people in the world now have the luxury to own both a mobile device and a personal computer for various purposes such as work. There has been a growing trend for people to view the files on the computer and transfer them to their mobile device on the go. At present, many users are still using the traditional method of file transfer using a cable connection and have long to have a way to automatically sync their files between two different devices. This project will look into this issue by creating an Android application that is able to automatically sync files between the PC and the Android device over the local WiFi network. The project will consist of an Android application and a Windows application. The user will be able to use the Android application to list the directories from the PC, perform file transfer and configure the directories of both devices to perform file syncing. Due to the complexity of the project, the project is divided into three different parts. This report will focus on the first part of the project where the majority of the implementation work and infrastructure of the both the Android application and the Windows application as well as the communication protocol between the two device will be developed. This report will also briefly talk about the implementation of the other parts of the project and how they are interlink with each other to form the entire purpose of the project.